Quality Evaluation of Yogurt Produced from Chili Pepper-Derived Starter Culture - EZEALOR, Mordecai C.; ORHEVBA, Bosede A.; OYEBAMIJI, Ruth O. (FUDMA Journal of Engineering and Technology, 2026)
The study investigated the production of yogurt using starter cultures developed from chili pepper and evaluated its effect on some quality parameters of the resultant yogurt. The quality parameters investigated were: nutritional content and sensory attributes. Statistical analysis, (ANOVA) and Duncan's multiple range test were applied to assess significant differences. The results revealed that the addition of chili pepper have significant effects (p
Keywords: Chili pepper, yogurt, starter culture, proximate composition, sensory evaluation.